MagnEtophoretic Slider Assay (MeSA): A simple platform for point-of-care diagnostics - Call, Zachary D.; Dolence, Alli; Boes, Jason; Henry, Charles S. (Frontiers in Sensors, 2023)
Infectious diseases account for millions of deaths each year. To reduce the number of infectious disease related deaths, diagnostic testing needs to be more accessible to patients in low-income countries as well as developed countries. Current diagnostic methods involve centralized laboratories, trained personnel, and are time-intensive, limiting translation to the point-of-care (POC). Microfluidic devices are a popular alternative for diagnostics due to reduced assay times, reduced sample volume, and lower cost. Microfluidic devices are small (<10 cm) and can perform complex assays. Microfluidic paper-based analytical devices (µPADs) are a popular approach to help translate diagnostics to the POC but historically suffer from poor sensitivity when compared to established laboratory methods. Magnetically labeling analytes allows samples to be sorted resulting in improved sensitivity and specificity. Microfluidic magnetophoresis is the process of manipulating magnetic particles in a magnetic field and offers the ability to wash and concentrate a sample during flow. However, until recently, magnetophoresis has not been used in conjunction with µPADs because magnetophoresis requires complex and expensive instrumentation to control flow. Coupling magnetophoresis with µPADs enables pump-free flow control, simple operation, and low cost. Early magnetophoresis µPADs showed detection limits similar to traditional methods but higher than targets for clinical use. In this work, we demonstrate a novel, simple MagnEtophoretic Slider Assay (MeSA) that is free of any external instrumentation and offers a new platform for POC diagnostics. We demonstrate the assay’s capability through biotin competitive assays and a sandwich immunoassay for E. coli detection. The calculated limit of detection for E. coli was 1.62 × 103 Colony Forming Units per mL (CFU/ml). The work described is a novel and simple microfluidic platform that has potential for a wide range of future applications.